The Effect of Pharmaceutical Care in the Management of Drug Related Problems in Hospitalized Geriatric Patients at Sanglah Hospital Denpasar - Andriani, Reza (Brawijaya University, 2019)
Drug related problems often occur in hospitalized geriatric patients, due to polypharmacy, multiple comorbidities, decreased organ function, pharmacokinetic and pharmacodynamic changes due to aging which can increase the risk of drug side effects and medication errors. The purpose of this study is to describe the Drug Related Problems (DRPs) and the characteristics of pharmaceutical care interventions in the geriatric ward of Sanglah General Hospital Denpasar. This study was conducted using retrospective data from primary sources in the form of DRPs, recorded in the Clinical Pharmacy Activity Report in the geriatric ward during the period of March to April 2017. The DRPs category follows the PCNE Classification scheme for Drug-Related Problems V5.01. 54 DRPs were found from 141 prescriptions reviewed for 150 patients. The reported DRPs include drug selection (29); duration of administration (12); interaction (10); dose (2) and adverse drug reactions (1). From the DRPs, a series of pharmaceutical care interventions for were done by pharmacists in the form of recommendations to the Physician. 54 recommendations were given and 46 of them were approved by the physician. The conclusion of this study shows the importance of the involvement of Pharmacists as caregivers in optimizing the pharmacotherapy of geriatric patients, and ensuring an effective, safe and efficient drug therapy.